A Bibliometric Analysis Sustainable Leadership in Higher Education - Tabara, Reijeng; Mariani, Mariani (LPPM Politeknik Saint Paul Sorong, 2025)
Sustainable leadership reveals the central role of leaders in balancing the three goals of economy, society, and environment and has become an important part of leadership theory research in recent years. The authors searched the literature related to sustainable leadership in higher education in the SCOPUS database. Based on the existing literature, we systematically reviewed the origins based on our predetermined criteria. And we also built an integrated analytical framework of sustainable leadership with the premise of sorting and summarizing the antecedents and consequences of sustainable leadership. Finally, we provide an outlook on the future research areas of sustainable leadership to further promote sustainable leadership research in higher education